Strategi Humas Pemprov Jatim Dalam Membangun Citra Pemerintahan Melalui Media Digital - Aprita Dwi Mardiyanti (LPPM Stikosa-AWS, 2023)
Public relations (PR) has an important function in building a good image for government agencies. The thing to do in building an image is to carry out a communication strategy that is friendly and responsive to the community. Based on the importance of public relations in the government, researchers want to examine how the government's public relations communication strategy builds an image in sharing information and sharing uploads of the activities of the Governor of East Java. This study focuses on the Instagram @humasprovjatim social media account owned by public relations which is more active than other social media owned by public relations. This type of research is qualitative-descriptive which describes the activities of public relations communication in providing information to the public. Researchers found a government public relations communication strategy in utilizing Instagram social media as a whole compared to other social media owned by East Java public relations such as Facebook, Twitter, Tiktok, Youtube.